2009
DOI: 10.3201/eid1509.080231
|View full text |Cite
|
Sign up to set email alerts
|

Highly Pathogenic Avian Influenza Virus A (H7N3) in Domestic Poultry, Saskatchewan, Canada, 2007

Abstract: Epidemiologic, serologic, and molecular phylogenetic methods were used to investigate an outbreak of highly pathogenic avian influenza on a broiler breeding farm in Saskatchewan, Canada. Results, coupled with data from influenza A virus surveillance of migratory waterfowl in Canada, implicated wild birds as the most probable source of the low pathogenicity precursor virus.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
45
0

Year Published

2010
2010
2017
2017

Publication Types

Select...
5
4
1

Relationship

1
9

Authors

Journals

citations
Cited by 73 publications
(45 citation statements)
references
References 12 publications
0
45
0
Order By: Relevance
“…Further studies indicated that a variety of charadriiform species are natural hosts of AIV [9,10,36 -38] and provide a reservoir for these viruses. [40]. AIV has been consistently isolated from birds (primarily from faecal samples) each year during the spring migration at Delaware Bay.…”
Section: Aiv and The Shorebirds Of Delaware Baymentioning
confidence: 97%
“…Further studies indicated that a variety of charadriiform species are natural hosts of AIV [9,10,36 -38] and provide a reservoir for these viruses. [40]. AIV has been consistently isolated from birds (primarily from faecal samples) each year during the spring migration at Delaware Bay.…”
Section: Aiv and The Shorebirds Of Delaware Baymentioning
confidence: 97%
“…In May 2002, an outbreak at a broiler breeder farm in Chile was identified and later controlled by depopulation and strict biosecurity (12). Outbreaks of H7N3 HPAI in commercial poultry operations in British Columbia and Saskatchewan, Canada, in 2004 and 2007, respectively, were reported to be caused by LPAI virus precursors from migratory waterfowl (13)(14)(15).…”
mentioning
confidence: 99%
“…Unlike Eurasian HPAI H5N1 and H7N7 viruses which typically possess traditional multibasic amino acid HA cleavage sites, these HPAI H7N3 viruses all appear to have arisen from LPAI precursor viruses by nonhomologous recombination between the HA and other viral genes or host cell genetic sequences (Berhane et al 2009; Maurer-Stroh et al 2013; Pasick et al 2005; Suarez et al 2004). To date, H7 viruses are the only known subtype to use this mechanism as a way to acquire a virulent phenotype.…”
Section: North American Lineage Virusesmentioning
confidence: 99%